Deep Electron Traps Responsible for Higher Quantum Efficiency in Improved GaN/InGaN Light Emitting Diodes Embedded with SiO2 Nanoparticles. (12th October 2016) - Polyakov, A. Y.; Smirnov, N. B.; Yakimov, E. B.; Cho, Han-Su; Baek, Jong Hyeob; Turutin, A. V.; Shemerov, I. V.; Kondratyev, E. S.; Lee, In-Hwan
Abstract : Deep traps spectra are compared for GaN/InGaN light emitting diodes with and without a template embedded with SiO2 nanoparticles underlying the active multiple quantum well region. The structures with SiO2 nanoparticles show a higher internal quantum efficiency which correlates with a lower concentration of deep traps with level near Ec -0.6 eV as compared to reference structures. We discuss complications in deep traps analysis coming from the freeze-out of Mg acceptors and the choice of proper biasing conditions for deep traps spectra analysis.